The regulation of MFG‐E8 on the mitophagy in diabetic sarcopenia via the HSPA1L‐Parkin pathway and the effect of D‐pinitol - Wenqian Zhao; Bin Zhao; Xinyue Meng; Baoying Li; Yajuan Wang; Fei Yu; Chunli Fu; Xin Yu; Xiaoli Li; Chaochao Dai; Jie Wang; Haiqing Gao; et al. (Journal of Cachexia, Sarcopenia and Muscle, 2024)
Abstract Background Diabetic sarcopenia is a disease‐related skeletal muscle disorder that causes progressive symptoms. The complete understanding of its pathogenesis is yet to be unravelled, which makes it difficult to develop effective therapeutic strategies. This study investigates how MFG‐E8 affects mitophagy and the protective role of D‐pinitol (DP) in diabetic sarcopenia. Methods In vivo, streptozotocin‐induced diabetic SAM‐R1 (STZ‐R1) and SAM‐P8 (STZ‐P8) mice (16‐week‐old) were used, and STZ‐P8 mice were administrated of DP (150 mg/kg per day) for 6 weeks. Gastrocnemius muscles were harvested for histological analysis including transmission electron microscopy. Proteins were evaluated via immunohistochemistry (IHC), immunofluorescence (IF), and western blotting (WB) assay. In vitro, advanced glycation end products (AGEs) induced diabetic and D‐galactose (DG) induced senescent C2C12 models were established and received DP, MFG‐E8 plasmid (Mover)/siRNA (MsiRNA), or 3‐MA/Torin‐1 intervention. Proteins were evaluated by IF and WB assay. Immunoprecipitation (IP) and co‐immunoprecipitation (CO‐IP) were used for hunting the interacted proteins of MFG‐E8. Results In vivo, sarcopenia, mitophagy deficiency, and up‐regulated MFG‐E8 were confirmed in the STZ‐P8 group. DP exerted protective effects on sarcopenia and mitophagy (DP + STZ‐P8 vs. STZ‐P8; all P < 0.01), such as increased lean mass (8.47 ± 0.81 g vs. 7.08 ± 1.64 g), grip strength (208.62 ± 39.45 g vs. 160.87 ± 26.95 g), rotarod tests (109.7 ± 11.81 s vs. 59.3 ± 20.97 s), muscle cross‐sectional area (CSA) (1912.17 ± 535.61 μm2 vs. 1557.19 ± 588.38 μm2), autophagosomes (0.07 ± 0.02 per μm2 vs. 0.02 ± 0.01 per μm2), and cytolysosome (0.07 ± 0.03 per μm2 vs. 0.03 ± 0.01 per μm2). DP down‐regulated MFG‐E8 in both serum (DP + STZ‐P8: 253.19 ± 34.75 pg/mL vs. STZ‐P8: 404.69 ± 78.97 pg/mL; P < 0.001) and gastrocnemius muscle (WB assay. DP + STZ‐P8: 0.39 ± 0.04 vs. STZ‐P8: 0.55 ± 0.08; P < 0.01). DP also up‐regulated PINK1, Parkin and LC3B‐II/I ratio, and down‐regulated P62 in gastrocnemius muscles (all P < 0.01). In vitro, mitophagy deficiency and MFG‐E8 up‐regulation were confirmed in diabetic and senescent models (all P < 0.05). DP and MsiRNA down‐regulated MFG‐E8 and P62, and up‐regulated PINK1, Parkin and LC3B‐II/I ratio to promote mitophagy as Torin‐1 does (all P < 0.05). HSPA1L was confirmed as an interacted protein of MFG‐E8 in IP and CO‐IP assay. Mover down‐regulated the expression of Parkin via the HSPA1L‐Parkin pathway, leading to mitophagy inhibition. MsiRNA up‐regulated the expression of PINK1 via SGK1, FOXO1, and STAT3 phosphorylation pathways, leading to mitophagy stimulation. Conclusions MFG‐E8 is a crucial target protein of DP and plays a distinct role in mitophagy regulation. DP down‐regulates the expression of MFG‐E8, reduces mitophagy deficiency, and alleviates the symptoms of diabetic sarcopenia, which could be considered a novel therapeutic strategy for diabetic sarcopenia.